Are detox juices a good source of nutrients? - Santos, I.C. (2018)
Abstract publicado em: Translational Research and Innovation in Human and Health Science, Annals of Medicine. 2018;50(Sup1):S119-20, doi:10.1080/07853890.2018.1427445